Does the stretching intensity matter when targeting a range of motion gains? a randomized trial - Amanda de Araújo Valença; Bárbara Oliveira Soares; Bruno Remígio Cavalcante; Natália Barros Beltrão; Vinicius Yan Santos Nascimento; Ana Carolina Rodarti Pitangui; Rodrigo Cappato de Araújo (Universidade Estadual Paulista (UNESP), 2020)
Abstract Aims: To verify the effects of flexibility training conducted at different intensities in young adults. Methods: Twenty-one (21) young adults of both genders with no history of surgery, fracture, and/or rheumatic diseases in the lower limbs and hip, were randomly assigned to low intensity (LI) or high intensity (HI) stretching groups. Two researchers were assigned to evaluate the active knee extension range of motion (ROM) of the volunteers and two other researchers were responsible for the training program. The training consisted of a single exercise for the hamstring muscles (biceps femoris, semimembranosus, semitendinosus). Each session consisted of three repetitions of passive static stretching, maintained for the 60s each, with 30s interval between them, and performed three times a week for four weeks. The stretching intensity was based on the Numerical Verbal Scale, the LI group maintained the intensity between 1 and 2, while the HI group between 9 and 10. Three ROM evaluations were performed pre-intervention, after the 6th session and at the end of the 12th session. Results: No difference was observed between the groups that underwent either high- or low-intensity programs. Both groups achieved gains in flexibility after four weeks of training. Conclusions: The study demonstrated that both high- and low-intensity stretching exercises are effective for ROM and there were no differences between them. Therefore, the intensity can be defined by the preference of the therapist or patient.